VD_FINDINFO AM 31/09 - 71/2011 vom 28. November 2011 - VD Tribunal cantonal (2011)
LOI FÉDÉRALE SUR L'ASSURANCE-MALADIE, CARACTÈRE DE MALADIE, ESTHÉTIQUE, OPÉRATION | 25 al. 1 LAMal, 25 al. 2 LAMal, 33 LAMal, 33 OAMal, 1 OPAS